Schistosomiasis is associated with incident HIV transmission and death in Zambia. - Kristin M Wall; William Kilembe; Bellington Vwalika; Cecile Dinh; Paul Livingston; Yeuk-Mui Lee; Shabir Lakhi; Debi Boeras; Htee Khu Naw; Ilene Brill; Elwyn Chomba; Tyronza Sharkey; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:We examined relationships between schistosome infection, HIV transmission or acquisition, and all-cause death. METHODS:We retrospectively tested baseline sera from a heterosexual HIV-discordant couple cohort in Lusaka, Zambia with follow-up from 1994-2012 in a nested case-control design. Schistosome-specific antibody levels were measured by ELISA. Associations between baseline antibody response to schistosome antigens and incident HIV transmission, acquisition, and all-cause death stratified by gender and HIV status were assessed. In a subset of HIV- women and HIV+ men, we performed immunoblots to evaluate associations between Schistosoma haematobium or Schistosoma mansoni infection history and HIV incidence. RESULTS:Of 2,145 individuals, 59% had positive baseline schistosome-specific antibody responses. In HIV+ women and men, baseline schistosome-specific antibodies were associated with HIV transmission to partners (adjusted hazard ratio [aHR] = 1.8, p<0.005 and aHR = 1.4, p<0.05, respectively) and death in HIV+ women (aHR = 2.2, p<0.001). In 250 HIV- women, presence of S. haematobium-specific antibodies was associated with increased risk of HIV acquisition (aHR = 1.4, p<0.05). CONCLUSION:Schistosome infections were associated with increased transmission of HIV from both sexes, acquisition of HIV in women, and increased progression to death in HIV+ women. Establishing effective prevention and treatment strategies for schistosomiasis, including in urban adults, may reduce HIV incidence and death in HIV+ persons living in endemic areas.